Depression and social isolation during the COVID-19 pandemic in a student population: the effects of establishing and relaxing social restrictions - Holm-Hadulla, Rainer Matthias; Wendler, Hannes; Baracsi, Gabriella; Storck, Timo; Möltner, Andreas; Herpertz, Sabine C. (Frontiers in Psychiatry, 2023)
In a quasi-naturalistic study design, we evaluate the change in psychopathological syndromes and general well-being after the alleviation of social restrictions. The aim of this study was to investigate the specific relationship between social isolation and depressive syndromes. Methods: At two timepoints, the first during maximal social restrictions, the second after social restrictions had widely ended for nine months, depressive and other syndromes were measured in an online survey addressing the total cohort of students registered at Heidelberg University, Germany via e-mail (n=27,162). The complete Patient Health Questionnaire (PHQ) was used with nine items for depressive syndromes. In addition, well-being was measured by the Well-Being Index WHO-5. In the quantitative and qualitative part of the study psychopathological syndromes and well-being were related to social isolation and feelings of loneliness. Results: After 1.5 years of pandemic-related social restrictions, "major" depressive syndromes were reported by 40.16% of the respondents to the PHQ in a sample of 2,318 university students. 72.52% showed a severely reduced Well-Being-Index. Nine months after the end of social restrictions, "major" depressive syndromes were reported by 28.50% of the participants. Well-being improved after the alleviation of social restrictions, as well: 53.96% showed a Well-Being Index of below 50 vs. 72.52% in the first study. The quantitative and qualitative analysis of the free texts of the respondents suggest that a significant amount of depressive syndromes and reduced well-being are related to social isolation and loneliness. While in the times of the pandemic restrictions the participants mostly reported "loneliness and social isolation" (24.2%) as their main problem, only 7.7% described these as their main problem after social restrictions had been loosened for nine months. The qualitative analysis hints that at t2 participants were more likely to mention possible ways to actively deal with loneliness than at t1, which might be interpreted along the lines of the decrease in depressive syndromes. Discussion: Keeping the self-selection bias in mind our study results suggest that one third of "major" depressive syndromes and one quarter of severely reduced well-being accompany social restrictions or are even caused by them, with loneliness being an important factor.